Taxonomic review of the genus Euboeus s. str. Boieldieu, 1865 (= Probaticus s. str. Seidlitz, 1896, syn. n.) (Coleoptera, Tenebrionidae) - Nabozhenko, M.v.; Nikitsky, N.b.; Keskin, B. (Zootaxa, 2017)
The taxonomic history and position of the genera Euboeus and Probaticus within the tribe Helopini are discussed. A new synonymy, based on morphological characters is established: Euboeus Boieldieu, 1865 = Probaticus (s. str.) Seidlitz, 1896, syn. n. As a result, 67 new combinations (from Probaticus to Euboeus) are estabished for all species formerly placed in Probaticus. A review of Euboeus s. str. with four species (Balkanian-Anatolian E. mimonti Boieldieu, 1865 and E. tentyrioides (Küster, 1851), Greek E. mori (Brullé, 1832), and Anatolian E. parvostriatus sp. n.) is given. Three new synonyms are established for Euboeus tentyrioides (= Micispa bysantica Motschulsky, 1858, syn. n.; = Micispa pyraei Motschulsky, 1858, syn. nov.; = Micispa graeca Motschulsky, 1858, syn. n.). The forgotten name Helops (Euboeus) parvicollis Baudi di Selve, 1876, nomen oblitum (junior synonym of E. tentyrioides) is discussed. A lectotype is designated for Helops tentyrioides. A key to the four species within the revised Euboeus sensu stricto, along with distributions and images, is provided.